Sustainable and scalable production of nanoporous carbon derived casein nanoparticles with high surface area for promising hydrogen storage capacity and CO2/H2 separation - Nour F. Attia; Alfonso Policicchio; Asmaa K. Mohamed; Carlo Poselle Bonaventura; Raffaele Giuseppe Agostino; Fatma A.-M. Kassem; Asmaa M. Zakria; Amal Alkahlawy; Sally E.A. Elashery (Chemical Engineering Journal, 2025)

Early Permian post-collisional magmatism induced by extensive removal of the Variscan lithospheric mantle - Andrea Boscaini; Joshua H. F. L. Davies; Morgann G. Perrot; Raffaele Sassi; Claudio Mazzoli; Angelo De Min; Corrado Morelli; Evelyn Kustatscher; Thomas Blanchet-Gavouyère; Andrea Marzoli (Contributions to Mineralogy and Petrology, 2025)

4D imaging of the volcano feeding system beneath the urban area of the Campi Flegrei caldera - Pietro Tizzani; José Fernández; Andrea Vitale; Joaquín Escayo; Andrea Barone; Raffaele Castaldo; Susi Pepe; Vincenzo De Novellis; Giuseppe Solaro; Antonio Pepe; Anna Tramelli; Zhongbo Hu; et al. (Remote Sensing of Environment, 2024)

Interregional imbalance in the Yellow River Basin: Insights from flood-sediment transport, socioeconomic, and environmental subsystems - Hao Hu; Guiliang Tian; Jan F. Adamowski; Raffaele Albano; Yixue Liu; Xiaodong Jing; Qiuya Zhao (Journal of Environmental Management, 2024)

Optimal resource reallocation can achieve water conservation, emissions reduction, and improve irrigated agricultural systems - Simeng Cui; Jan F. Adamowski; Raffaele Albano; Mengyang Wu; Xinchun Cao (Agricultural Systems, 2024)

Feed restriction during the suckling period of ewe Assaf lambs (F0) modifies milk quality and milk exosomal miRNAome of the filial generation (F1) - Alba Martín; Carlos García-Estrada; Estela Melcón-Fernández; Raffaele A. Calogero; Maddalena Arigoni; Fabrizio Ceciliani; Cristina Lecchi; Mahsa Dehnavi; F. Javier Giráldez; Sonia Andrés (Animal Feed Science and Technology, 2024)

In silico, in vitro, and in vivo human metabolism of acetazolamide, a carbonic anhydrase inhibitor and common “diuretic and masking agent” in doping - Francesco P. Busardò; Alfredo F. Lo Faro; Ascanio Sirignano; Raffaele Giorgetti; Jeremy Carlier (Archives of Toxicology, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

A first-of-its-kind multi-model convection permitting ensemble for investigating convective phenomena over Europe and the Mediterranean - Erika Coppola; Stefan Sobolowski; E. Pichelli; F. Raffaele; B. Ahrens; I. Anders; N. Ban; S. Bastin; M. Belda; D. Belusic; A. Caldas-Alvarez; R. M. Cardoso; et al. (Climate Dynamics, 2020)

On the Future of Argo: A Global, Full-Depth, Multi-Disciplinary Array - Dean Roemmich; Matthew H. Alford; Hervé Claustre; Kenneth Johnson; Brian King; James Moum; Peter Oke; W. Brechner Owens; Sylvie Pouliquen; Sarah Purkey; Megan Scanderbeg; Toshio Suga; et al. (Frontiers in Marine Science, 2019)

Linking sardine recruitment in coastal areas to ocean currents using surface drifters and HF radar: a case study in the Gulf of Manfredonia, Adriatic Sea - Roberta Sciascia; Maristella Berta; Daniel F. Carlson; Annalisa Griffa; Monica Panfili; Mario La Mesa; Lorenzo Corgnati; Carlo Mantovani; Elisa Domenella; Erick Fredj; Marcello G. Magaldi; Raffaele D'Adamo; et al. (Ocean Science, 2018)
Understanding the role of ocean currents in the recruitment of commercially and ecologically important fish is an important step toward developing sustainable resource management guidelines. To this end, we attempt to elucidate the role of surface ocean transport in supplying recruits of European sardine (Sardina pilchardus) to the Gulf of Manfredonia, a known recruitment area in the Adriatic Sea. Sardine early life history stages (ELHSs) were collected during two cruises to provide observational estimates of their age–size relationship and their passive pelagic larval duration (PPLD). We combine these PPLDs with observations of surface ocean currents to test two hypotheses: (1) ELHSs are transported from remote spawning areas (SAs) by ocean currents to the Gulf of Manfredonia; (2) sardines spawn locally and ELHSs are retained by eddies. A historical surface drifter database is used to test hypothesis 1. Hypothesis 2 is tested by estimating residence times in the Gulf of Manfredonia using surface drifters and virtual particles trajectories that were computed from high-resolution observations of surface currents measured by a high-frequency (HF) radar network. Transport to the Gulf of Manfredonia from remote SAs seems more likely than local spawning and retention given a mismatch between observed PPLDs of 30–50 days and relatively short (

Marine protist diversity in E uropean coastal waters and sediments as revealed by high‐throughput sequencing - Ramon Massana; Angélique Gobet; Stéphane Audic; David Bass; Lucie Bittner; Christophe Boutte; Aurélie Chambouvet; Richard Christen; Jean‐Michel Claverie; Johan Decelle; John R. Dolan; Micah Dunthorn; et al. (Environmental Microbiology, 2015)
Summary Although protists are critical components of marine ecosystems, they are still poorly characterized. Here we analysed the taxonomic diversity of planktonic and benthic protist communities collected in six distant E uropean coastal sites. Environmental deoxyribonucleic acid ( DNA ) and ribonucleic acid ( RNA ) from three size fractions (pico‐, nano‐ and micro/mesoplankton), as well as from dissolved DNA and surface sediments were used as templates for tag pyrosequencing of the V4 region of the 18S ribosomal DNA. Beta‐diversity analyses split the protist community structure into three main clusters: picoplankton‐nanoplankton‐dissolved DNA , micro/mesoplankton and sediments. Within each cluster, protist communities from the same site and time clustered together, while communities from the same site but different seasons were unrelated. Both DNA and RNA ‐based surveys provided similar relative abundances for most class‐level taxonomic groups. Yet, particular groups were overrepresented in one of the two templates, such as marine alveolates ( MALV )‐ I and MALV‐II that were much more abundant in DNA surveys. Overall, the groups displaying the highest relative contribution were Dinophyceae, Diatomea, Ciliophora and Acantharia. Also, well represented were Mamiellophyceae, Cryptomonadales, marine alveolates and marine stramenopiles in the picoplankton, and Monadofilosa and basal F ungi in sediments. Our extensive and systematic sequencing of geographically separated sites provides the most comprehensive molecular description of coastal marine protist diversity to date.

Re-Defining Canis etruscus (Canidae, Mammalia): A New Look into the Evolutionary History of Early Pleistocene Dogs Resulting from the Outstanding Fossil Record from Pantalla (Italy) - Marco Cherin; Davide F. Bertè; Lorenzo Rook; Raffaele Sardella (Journal of Mammalian Evolution, 2014)

Cellular and molecular effects of protons: Apoptosis induction and potential implications for cancer therapy - C. Di Pietro; S. Piro; G. Tabbì; M. Ragusa; V. Di Pietro; V. Zimmitti; F. Cuda; M. Anello; U. Consoli; E. T. Salinaro; M. Caruso; C. Vancheri; et al. (Apoptosis, 2006)